Synthesis, Structure, and Cyclic Voltammetric Studies of [CpFeC5H4CCAlNCH2(C4H3S)]6: The First Model Compound for the Fixation of Metal-Containing Ligands on an Aluminum Nitride Cluster - Srisailam, Shravan Kumar; Reddy, N. Dastagiri; Roesky, Herbert W.; Vidovic, Denis; Magull, Jörg; Winter, Rainer F. (My University, 2003)
An Al−N cluster containing an assembly of six ferrocenylacetylene moieties has been synthesized and structurally characterized. The electrochemical behavior of this compound shows a single reversible oxidation wave, which suggests the electrochemical equivalence of the ferrocenylacetylene moieties.
Keywords: 540